Personality and stress coping styles of dancesport athletes - Kowal, Paulina (Studia Psychologica: Theoria et praxis, 2011)
The following article presents the theoretical basis and practical reasons related to the concept of personality and stress coping styles. Sport dance is not yet popular in the field of Psychology of Sports. Dancing is often referred to in the literature as a form of art. The aim of the study was to present a psychological profile of the dancer as an athlete. Dominant personality traits and styles of coping with stress among the dancers are indicated in this paper. Also differences between men and women who are committed to continually work together as a dance couple are shown. 94 dancers were studied (W-46, M-48), aged 15-24 years (mean age 17 years, standard deviation 2.25). Subjects presented different levels of advancein sports, meaning they have different dance class which definesa skill of a dancer. They had also diversified dance training time, calculated as the number of trained years. Subjects came from nine Polish dance clubs. In the study were used: NEO-FFI Personality Inventory of Costa &McCrae and Coping Inventory of Stressful Situations of Endler& Parker. In order to obtain additional data and personal information related to the training process of dancers a surveyconstructed by the author was used. The results show the differences between women and men in terms of personality traits and stress coping styles. Women show a style focused on avoiding the stressful situation and seek social contact more than men. Women are agreeable and conscientious. Studies also show a correlation between age and type of coping style in a difficult situation. Older dancers are more focused on the task, while the younger focus on experienced emotions, avoiding the task or problem, engage in alternative activities. In addition, studies have found an importanceof advancement of sport styles in somestress coping styles and in selected personality traits. The dancers with a higher dancing class, that are more advanced present style of coping with stress concentrated on the task, less advanced dancers are more emotional and neurotic.